2021
DOI: 10.1289/ehp8036
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a MIND-Like Dietary Pattern, Long-Term Exposure to Fine Particulate Matter Air Pollution, and MRI-Based Measures of Brain Volume: The Women’s Health Initiative Memory Study-MRI

Abstract: Background: Previous studies suggest that certain dietary patterns and constituents may be beneficial to brain health. Airborne exposures to fine particulate matter [particulate matter with aerodynamic diameter ( )] are neurotoxic, but the combined effects of dietary patterns and have not been investigated. Objectives: We examined whether previously reported association between exposure and lower white matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 83 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…However, we cannot rule out the possibility that regional differences could be partly due to gene-environment interaction 48 and/or interactions with various nongenetic factors including diet. 49 The differential effects across regions emphasize the value of taking a geographic approach in large studies. Thus, we encourage the application of this approach in other parts of the world, including densely populated regions in South Asia where PM 2.5 levels can reach ;60 μg/m 3 on average 50 (compared with 14 μg/m 3 for the contiguous United States at the time of our study).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot rule out the possibility that regional differences could be partly due to gene-environment interaction 48 and/or interactions with various nongenetic factors including diet. 49 The differential effects across regions emphasize the value of taking a geographic approach in large studies. Thus, we encourage the application of this approach in other parts of the world, including densely populated regions in South Asia where PM 2.5 levels can reach ;60 μg/m 3 on average 50 (compared with 14 μg/m 3 for the contiguous United States at the time of our study).…”
Section: Discussionmentioning
confidence: 99%
“…The MIND diet has been linked to slower cognitive decline 16 and lower risks of all‐cause dementia 17 and Parkinson's disease, 18 but only several cross‐sectional studies have assessed its associations with brain structural markers. In 1302 participants of the Women's Health Initiative Memory Study, adherence to a MIND‐like diet was associated with higher total and temporal lobe white matter volumes 20 . In 175 older adults in France, a higher MIND diet score was associated with lower diffusivity values in the splenium of the corpus callosum 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, associations of the MIND diet with brain structural markers remain unclear and inconsistent, and elucidating these relationships is crucial for understanding the mechanisms linking this dietary pattern to brain aging. Among 1302 Women's Health Initiative participants, a higher MIND diet score was associated with higher total and temporal lobe white matter volumes 20 . In 175 French individuals, a higher MIND diet score was associated with lower diffusivity in the splenium of the corpus callosum 21 .…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, we found that all considered diet quality scores were associated with larger volumes of several specific regions (e.g., parietal and temporal cortex, and hippocampus), but not with total volumes of the total brain (i.e., GM and WM), GM, and WM. To date, limited studies have explored the associations of diet quality scores including MDS 21 48-50 , RFS 50 , MIND 44 51 52 , and AHEI-2010 53 with brain structures, mainly among older adults with a relatively small sample size 21 44 48 49 54 , and reported mixed results. With over 25,000 middle-aged and older adults, this study revealed discrepancies in various diet quality scores.…”
Section: Discussionmentioning
confidence: 99%